Keseimbangan emosional Miskawaih: Strategi psikologis pengendalian nafsu (bahimiyyah) dan emosi (sabuiyyah) dengan perspektif rasional - Rahmawati, Ravita Nisa; Azkiya, Nadya Nurul; Ashshoodiq, Ja’far (Maliki Interdisciplinary Journal, 2026)
This article examines Ibn Miskawaih’s concepts of controlling desire (al-nafs al-bahimiyyah) and emotion (al-nafs al-sabū‘iyyah) from a rational perspective. Using a qualitative method through library research, this study analyzes Miskawaih’s theory of the human soul, which consists of three faculties: reason (al-nafs al-nāṭiqah), emotion, and desire. The discussion focuses on two instinctive faculties that strongly influence human behavior. Findings indicate that moral and emotional balance can only be achieved when reason functions as the primary regulator, guiding both desire and anger to remain within proper limits. Self-control is developed through habituation, continuous training, self-evaluation, behavioral modification, and creating a supportive environment, all of which align with the principle of the “middle path” (al-wasath). This study concludes that Miskawaih’s approach to self-regulation aligns with modern psychological theories of emotional regulation, making it relevant for enriching Islamic ethical studies and the development of human character.